A experiência da reciclagem no município de Aracaju/SE : os bairros Inácio Barbosa e Siqueira Campos. - Nascimento, Edna Maria do (2007)
This research presents an analysis on the recyclable productive chain in Aracaju/Se, it focalizes two great districts of the city Inácio Barbosa and Siqueira Campos. The objective of the research was analyze the management of the non-organic domiciliar garbage from its generation to its destiny in the recyclable process, in order to identify the possible factors that harm the efficiency and efficacy in the administration of the solid residues. For that, they were close to applied questionnaires the three main managers of the solid residues municipal district, and accomplished structured interviews and non-structured with the main ones involved and with the population of the districts chosen as sample space. It stood out the development as an increase production factor of solid residues, focusing the importance implementation of public politics adopted in the management of the non-organic domiciliar garbage, from its generation to its destiny to the recyclable process, and the environmental and economic impacts in those politics. The research showed that the management program of solid residues faces serious problems, due to the reduced material number collected recyclable and the competition with other actors of the chain of the recyclable, it recommends planning guidelines and operalization program and the implementation of more efficient public politics than they facilitate a larger access to the information and the environmental education of the population, integrating the environmental, social and economic factors in the management of the residues solid non-organic domiciliars.